2008
DOI: 10.1103/physrevlett.101.037207
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Theory of Gilbert Damping

Abstract: The magnetization dynamics of a single domain ferromagnet in contact with a thermal bath is studied by scattering theory. We recover the Landau-Liftshitz-Gilbert equation and express the effective fields and Gilbert damping tensor in terms of the scattering matrix. Dissipation of magnetic energy equals energy current pumped out of the system by the time-dependent magnetization, with separable spin-relaxation induced bulk and spin-pumping generated interface contributions. In linear response, our scattering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
174
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 26 publications
5
174
1
3
Order By: Relevance
“…As pointed out by Brataas et al [7], their approach is completely equivalent to a formulation in terms of the linear response or Kubo formalism. The latter route is taken in this communication that presents a Kubo-Greenwoodlike expression for the Gilbert damping parameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Brataas et al [7], their approach is completely equivalent to a formulation in terms of the linear response or Kubo formalism. The latter route is taken in this communication that presents a Kubo-Greenwoodlike expression for the Gilbert damping parameter.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice, like many other models it depends on a relaxation time parameter τ that describes the rate of transfer due to the various types of possible scattering mechanisms. This weak point could be removed recently by Brataas et al [7] who described the Gilbert damping by means of scattering theory. This development supplied the formal basis for the first parameter-free investigations on disordered alloys for which the dominant scattering mechanism is potential scattering caused by chemical disorder [8].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12]14,20 The dissipation of magnetic energy accompanying the slow magnetization dynamics, evaluated within a scattering theory or the Kubo linear response formalism, leads also to explicit expressions for the Gilbert damping tensor. 13,[17][18][19] Most of these formulations yield relations equivalent to the so-called torquecorrelation formula…”
Section: Introductionmentioning
confidence: 99%
“…A large number of theoretical approaches to the Gilbert damping has been worked out during the last two decades; here we mention only schemes within the oneelectron theory of itinerant magnets, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] where the most important effects of electron-electron interaction are captured by means of a local spin-dependent exchangecorrelation (XC) potential. These techniques can be naturally combined with existing first-principles techniques based on the density-functional theory, which leads to parameter-free calculations of the Gilbert damping tensor of pure ferromagnetic metals, their ordered and disordered alloys, diluted magnetic semiconductors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gilmore and Stiles 2 as well as Thonig et al 12 demonstrated a generalized torque correlation model that includes both intraband (conductivity-like) and interband (resistivity-like) transitions. The use of scattering theory to describe damping was later applied by Brataas et al 13 and Liu et al 14 to describe damping in transition metals. A numerical realization of a linear response damping model was implemented by Mankovsky 3 for Ni-Co, Ni-Fe, Fe-V and Co-Fe alloys.…”
mentioning
confidence: 99%